A sub-fossil coral Sr∕Ca record documents northward shifts of the Tropical Convergence Zone in the eastern Indian Ocean - M. Pfeiffer; H. Takayanagi; H. Takayanagi; L. Reuning; T. K. Watanabe; T. K. Watanabe; S. Ito; D. Garbe-Schönberg; T. Watanabe; T. Watanabe; T. Watanabe; C.-C. Wu; et al. (Climate of the Past)
Sea surface temperature (SST) variability in the south-eastern tropical Indian Ocean is crucial for rainfall variability in Indian Ocean rim countries. A large body of literature has focused on zonal variability associated with the Indian Ocean Dipole (IOD) which peaks in austral spring. In today's climate, northward shifts of the Tropical Convergence Zone (TCZ) co-vary with the IOD, and it is unclear whether these shifts may also occur independently. We have developed a new monthly resolved Sr/Ca<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="33pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="b2a006b9788c1eb325815616d85bb8f7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-211-2025-ie00004.svg" width="33pt" height="14pt" src="cp-21-211-2025-ie00004.png"/></svg:svg> record from a sub-fossil coral cored at Enggano Island (Sumatra, Indonesia). Core sections containing diagenetic phases are omitted from the SST reconstruction. U/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="57ee8123d9c9aefcf23d9c7f6463c158"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-211-2025-ie00005.svg" width="8pt" height="14pt" src="cp-21-211-2025-ie00005.png"/></svg:svg>Th dating shows that the Sr/Ca<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="33pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="90dc7a8a55bd37b8673bdad01c3cf421"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-211-2025-ie00006.svg" width="33pt" height="14pt" src="cp-21-211-2025-ie00006.png"/></svg:svg>-based SST record extends from 1869–1918 and from 1824–1862 with a relative age uncertainty of ±3 years (2σ). At Enggano Island, coastal upwelling and cooling in austral spring impact SST seasonality and are coupled to the latitudinal position of the TCZ. The sub-fossil coral indicates an increase in SST seasonality between 1856 and 1918 relative to the 1930–2008 period. We attribute this to enhanced cooling due to stronger south-easterly (SE) winds driven by a northward shift in the TCZ in austral spring. A nearby sediment core indicates colder SSTs and a shallower thermocline prior to ∼1930. These results are consistent with an increase in the north–south SST gradient in the eastern Indian Ocean, calculated from historical temperature data, that is not seen in the zonal SST gradient. We conclude that the relationship between meridional and zonal variability in the eastern Indian Ocean is non-stationary and modulated by the long-term evolution of temperature gradients.